Living with a label: an action oriented feminist inquiry into women's mental health - Gray, Jennie (Curtin University, 2006)
Dorothy Smith (1987) says investigations often begin with ‘a feeling of uneasiness’. Smith’s insistence of the importance of starting with women’s standpoint, to redress the way in which women’s lives have been negated or neglected in research, informs the methodological premise of this inquiry. The unease that prompted this project emerged in conversations I had with women diagnosed with a psychiatric disorder whilst working as a practitioner at a women’s health centre. The frequency with which the discourses of biomedicine figured in these women’s narrated experiences engendered a collective commitment to make problematic ‘living with a label’. Loosely connected as mental health service recipients, the women I researched with are often positioned as ‘subject’ to an objective medical gaze. Disrupting dichotomies that these women are accustomed to in clinical settings, and destabilising notions of neutral and detached research, our investigations were contingent, reflexive and relational. Recognising that all were intrinsic to the knowledge production processes, this project was cast in the feminist ‘with’, rather than the ‘on’. Together we explored how women read and respond to a psychiatric diagnosis in their daily lives, to generate understandings that can be used by the women who joined this project. This included close consideration of social relations shaping the lived actualities these women described, and their agency in sustaining and unsettling these.Acknowledging these women’s capacity to have expertise not only as reporters, but as theorists too, experience and analysis were conflated in our explorations of ‘living with a label’. Congruent with feminist philosophy, our methodology had a praxis orientation as well, ‘to produce different knowledge and to produce knowledge differently’ as Patti Lather (2001) suggests. The attendant opportunities to research the process of researching and contemplate how we might participate in change-oriented activities were thus integral to this project. Our experience of researching together, and allowing the ‘researched’ room to know and act, produced possibilities, and also created conundrums, perhaps less frequently encountered in more conventional research – all of which gave rise to celebration!